PERJANJIAN PEMBIAYAAN KONSUMEN DENGAN JAMINAN FIDUSIA DALAM PERJANIAN PADA PT.ADIRA DINAMIKA MULTIFINANCE Tbk CABANG PADANG - , Roni Putra, Taufiq El Rahman,SH,M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research on Consumer Financing Agreement with Fiduciary Guarantee Agreement On PT.Adira Dynamics Branch Field Multifinance Tbk aims to find out the factors that cause the occurrence of bad credit and an attempt to solve the bad credit dynamics PT.Adira Multifinance Tbk Branch Field. This study is an empirical research juridical or juridical sociological research, which in conducting the study, researchers compared the provisions in force in accordance with the will of the law in the state of law enforcement in the field. Primary data and secondary data obtained through field research and library research. The data were analyzed qualitatively and presented descriptively. The results showed: 1. Prose lending in PT.Adira Branch Padang is not in accordance with the applicable provisions and regulations applicable in PT.Adira Dynamics Multifinace because marketing officer conduct in the performance deviation due to the credit granting process because the high targets set by the company and also affect the monthly incentive marketing so running the marketing in the process did not survey the field and even falsify the data of borrowers. Where unnoticed by the marketing impact of these deviations are nonperforming loans in PT.Adira Padang.2 Branch. with respect to non-performing loans in PT Adira Branch Padang, the company doing the billing efforts with the power given to the deb collector who worked with PT.Adira Branch Padang and the company does not escape from the constraints in the credit settlement received a subpoena from the debtor, which is represented by BPSK (Dispute Settlement Body). In the implementation of new fiduciary registration done by PT.Adira Branch Padang problematic if credit and received a subpoena from the debtor that is not in accordance with the provisions of the Act fiduciary that the fiduciary be registered at the time of signing the loan agreement.